2021
DOI: 10.21608/edj.2020.50258.1348
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bioceramic Sealers on the Fracture Resistance of Endodontically Treated Teeth (In Vitro Study)

Abstract: This study aimed to evaluate the effect of bioceramic sealers on the fracture resistance of endodontically treated teeth compared to resin-based sealers and zinc oxide and eugenol based sealers. Methods: Seventy (n=70) freshly human extracted single rooted teeth were selected. The samples were biomechanically prepared and classified according to the type of the sealer used into four groups as follows; Group 1 (n=21) obturated with gutta-percha and Endofill sealer (Dentsply, Germany). Group 2 (n=21) obturated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Furthermore, bioceramic sealer has slow setting and when it is combined with the sluggish expansion of C-points when subjected to moisture, may have possibly pushed the sealer into spaces AH Plus sealer with gutta-percha could not reach (26) . This came in agreement with Nagas et al (25) , Patil et al (27) and Elfaramawy and Abdelrahman (28) who reported that the calcium silicate composition of bioceramic sealer helps in minimizing contraction during the setting procedure. Also, its bonding effectiveness to root canal dentin might be due to the extremely small particle size and the low level of viscosity of bioceramic sealer which improves its flow.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, bioceramic sealer has slow setting and when it is combined with the sluggish expansion of C-points when subjected to moisture, may have possibly pushed the sealer into spaces AH Plus sealer with gutta-percha could not reach (26) . This came in agreement with Nagas et al (25) , Patil et al (27) and Elfaramawy and Abdelrahman (28) who reported that the calcium silicate composition of bioceramic sealer helps in minimizing contraction during the setting procedure. Also, its bonding effectiveness to root canal dentin might be due to the extremely small particle size and the low level of viscosity of bioceramic sealer which improves its flow.…”
Section: Discussionsupporting
confidence: 90%